The success of critical velocity protocol on predicting 10000 meters running performance - Barış Çabuk; Onur Demirarar; Merve Cin; Refik Çabuk; Bahtiyar Özçaldıran (Physical Education of Students, 2023)
Background and Study Aim. The study aims to evaluate which of the critical velocity (CV) estimates of the three widely used models and the best-fit model successfully predict the running performance of 10000 meters.